Determining the Genetic Markers of Schizophrenia using Molecular Diagnosis - Ismaeel, Haneen M.; Badro, Hayba; Khazaal, Ali Q.; Ahmed, Najwa Shihab (Iraqi Journal of Science, 2024)
Schizophrenia poses a considerable disease burden, notwithstanding its relatively low incidence rate. The escalation in population size and mean age has led to a substantial rise in the incidence of illness linked to schizophrenia, particularly in countries with moderate levels of prosperity. Therefore, it is necessary to find a way to detect and recognize the illness as fast as possible to stop the consequences from occurring and stop symptoms from appearing before they even start. Within this study’s scope, fifteen distinct primers were selected randomly to determine whether or not they could recognize schizophrenia. To accomplish this, a Randomly Amplified Polymorphic DNA-polymerase chain reaction (RAPD-PCR) was conducted utilizing DNA samples obtained from individuals afflicted with the condition and those in good health. The outcomes of the gel electrophoresis and subsequent analysis revealed that solely three primers including C12, E02 and E03 exhibited monomorphic characteristics. However, it was observed that 80% of the primers, precisely eleven out of fifteen, exhibited polymorphism. The results indicated that among the 15 primers tested, the primer labeled as H01 failed to generate any detectable bands. Subsequent examination of the polymorphic primers revealed that the primer efficiency varied between 0 and 0.0755, while the discrimination power ranged from 0 to 20 percent. The study observed variations in the frequency of disease occurrence between patients and healthy individuals. H05 primer utilization yielded three distinct polymorphic bands exhibiting diverse lengths. The band exhibiting the greatest length measured 1190 bp, whereas the other two bands had 480 and 430 bp lengths respectively. The two polymorphic bands exhibited 100% prevalence in the patient population while being completely absent in the healthy control group. Based on the available data, it appears that utilizing this primer to identify schizophrenia is a valid and valuable claim. Overall, DNA-based diagnostics may overlook a number of difficulties as laboratories have the ability to extract DNA from various sources easily. In this scenario, molecular and genetic techniques may be crucial for diagnosing some diseases.